Uma Investigação da gestão logística de empresas franqueadas do setor de moda feminina: estudo de caso de uma empresa franqueada de calçados e bolsas para mulheres - Rodrigues, Francisco Daniel Santiago (2016)
This work deals with companies working with sales of women's fashion. Based on the investigation of a franchised company selling ladies shoes and handbags, it researches the logistics management of franchised companies in this area. A benchmarking with franchised companies in other sectors was conducted to support the generalization of common actions. It starts with the characterization of the footwear industry, the economic relevance of this industrial sector, a bibliographical survey of the concepts of its logistics management practices, and also the definitions, relationships and dynamics involving franchising as a business model. In methodological terms, this research is classified as descriptive, exploratory, bibliographic and qualitative, using a case study. The collection of data was done by researching company's documents, by personal observation, and by structured interviews with professionals in the areas of interest. The investigation characterized the company in study, identified practices and logistics concepts used, and showed the deviations from the state of the art in logistics management. Within the results, it was possible to draw up a list of actions common to franchised businesses working with women's fashion As main results, there are considerations of ways to make operational improvements and to visualize new opportunities to increase the service level offered by the stores to the customers, as well as for the logistics management of the franchisee.